Institutional Challenges and Continuous Pending on Levying Excise on the Use of Plastics in Indonesia - Irmadra Fransiska Ginting; Maria R.U.D. Tambunan (School of Postgraduate Studies, Diponegoro Univer, 2024)
In response to the mounting plastic waste issue, the Indonesian government has introduced various measures aimed at curbing plastic usage, but these initiatives have fallen short in altering public behavior. A more impactful strategy would involve implementing a disincentive by levying additional fees on plastic use, effectively increasing its cost. Discussions on a plastic excise were initiated between the Indonesian government and the House of Representatives but have since stalled. This study aims to higlight the necessity of a plastic excise in regulating the behavior of Indonesian citizens and explores the appropriate methods for the government to formulate such an excise policy. A qualitative research method was employed, utilizing thorough interviews and extensive literature review. Findings suggest that the environmental damage inflicted by plastic waste justifies its classification as taxable goods, warranting regulatory control over its consumption due to the adverse effects on society and ecology. These findings serve as the foundation for the government to consider a plastic excise. The challenge lies in identifying the specific plastic types to be taxed, necessitating renewed coordination and dialogue with the pertinent Ministries and Agencies within the Inter-Ministerial Committee. This is essential to gain the Indonesian House of Representatives' approval and to address the complexities in policy formulation, considering that state levies shall be approved by the parliement. A possible solution to this challenge is to synchronize the taxable goods' plastic types with those outlined in the existing regulations of the Waste Reduction Roadmap by Producers, ensuring consistency and regulatory alignment.